A Note on Sturm-Liouville Problem for Difference Equations - Bas, Erdal; Ozarslan, Ramazan (E D P Sciences, 2017)
In this study, Sturm-Liouville delay difference equation is considered with initial conditions as follows -Delta(2)x(n-1)+q(n)x(n-k) = lambda x(n) x(1) = x(2) = 1 where k is an element of Z(+), n is a finite integer. Sum representation is found and from here, behaviors of eigenfunctions are investigated for different k values by illustrating with graphs and tables.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY